Must see places of the world. 4, Australia the beautiful [videorecording (DVD)] - Ford, Alice; Deere, Bob; Dalton, Tina; Steer, Gary; Waters, John, 1948- (Reader's digest classic collection., 2009)
Three programs on the natural wonders of Australia, covering the Great Barrier Reef, the Australian Alps, Daintree, Lord Howe Island, Shark Bay, King's Canyon, Flinders Ranges, Lake Eyres, Kakadu, the Blue Mountains, and Lamington's primeval rainforest.